In-lake measures for phosphorus control: The most feasible and cost-effective solution for long-term management of water quality in urban lakes. (15th June 2016) - Huser, Brian J.; Futter, Martyn; Lee, Jeff T.; Perniel, Mike
Abstract: Both in-lake and catchment measures designed to reduce phosphorus (P) loading were implemented as part of a 12.3 million USD restoration project for the Minneapolis Chain of lakes in Minnesota (USA). Treatment wetlands, 'in-pipe' measures, and in-lake aluminum sulfate (alum) treatment were applied to restore water quality in the four urban lakes. Different alum dosing methods led to between 4 and 20+ (modeled) years of water quality improvements in these lakes after treatment and only one of the four lakes continues to meet water quality goals approximately 25 years after the project started. Due to limited space and poor performance, reduction of total external loads was low (1–13%) for three lakes. Changes to internal P sediment release rates after application of alum correlated well with epilimnetic total P (TP) concentrations in these lakes, indicating that improvements in water quality were mainly driven by reduced internal loading via in-lake measures. Substantial reductions to external P loading were only achieved at Cedar Lake (49%) via conversion of an existing natural area to a treatment wetland, but even Cedar Lake is no longer meeting management goals. When expressed in terms of dollars spent per unit P removed, in lake alum treatment was on average 50 times more effective than in-catchment measures. The results of this study indicate that substantial external nutrient reductions may not be adequate to sustainably maintain water quality in urban lakes and that continued in-lake management of P accumulated in lake sediment will not only be necessary, but will also be more cost efficient relative to in-catchment measures. Highlights: Aluminum treatment initially improved TP, Secchi depth, and chl a in all lakes. External P reduction was not adequate to sustain water quality improvements. Space limitation around urban lakes restricted external P measures. Better monitoring programs are needed to assess treatment outcomes.